Moisture-curable composition for forming a cured product for applying a topcoat layer to a surface

By using polyaminosilanes of polyamino and ethoxy groups as tackifiers in polyoxyolefin polymer sealing materials, the problem of poor adhesion to the top coating is solved, and a high adhesion and stable laminate is achieved.

JP7628520B2Active Publication Date: 2025-02-10WACKER ASAHIKASEI SILICONE
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022099971
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-06-22
Publication Date
2025-02-10
Estimated Expiration
2040-11-18

AI Technical Summary

Technical Problem

When the conventional polyoxyalkylene polymer sealing material containing reactive silicone groups forms a top coating on the surface, there is a problem of poor adhesion, especially lack of adhesion to the solvent-based acrylate urethane top coating.

Method used

The adhesion of the silanized modified polymer containing the polyoxyalkylene polymer is improved by introducing a multiple amino group and an ethoxy group on the end groups of the silanized modified polymer to improve the adhesion to the top coating by introducing a plurality of amino groups and ethoxy groups on the end groups of the silanized modified polymer.

Benefits of technology

The adhesion between the siliconized modified polymer and the top coating is significantly improved, and the peeling of the top coating is avoided, and a stable laminate is formed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628520000001
    Figure 0007628520000001
Patent Text Reader

Abstract

The present invention relates to -CH2-SiR 1 a (OR 2 ) 3-a The present invention aims to provide a moisture-curable composition for forming a cured product that exhibits good adhesion to a top coat layer, even when using a silane-modified polymer A that is a polyoxyalkylene polymer having a terminal group represented by the formula: a method for bonding a cured product obtained by curing the moisture-curable composition to a top coat layer, a laminate including the cured product and the top coat layer, and a method for producing the same. The present invention uses a moisture-curable composition containing a silane-modified polymer A and an aminosilane B having two or more amino groups and one or more alkoxy groups having two or more carbon atoms.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to -CH2-SiR 1 a (OR 2 ) 3-a The present invention relates to a cured product obtained by curing a moisture-curable composition containing a silane-modified polymer having a terminal silyl group that can be crosslinked by hydrolysis, represented by the formula: and a specific aminosilane; a laminate including a substrate, the cured product, and a top coat layer; a method for bonding the cured product and the top coat layer; and a method for producing the laminate. [Background technology]

[0002] Known types of sealants include silicone-based sealants, modified silicone-based sealants, and polyurethane-based sealants. Silicone sealants, which are primarily composed of silicone (organopolysiloxane), generally have poor surface compatibility for painting, making it difficult to form a topcoat layer on the surface of the silicone sealant. On the other hand, modified silicone sealants, whose main component is a polyether with a silyl group at the end, are more compatible with paint than silicone sealants and often allow for the easy formation of a topcoat layer on the sealant surface, making them industrially useful. In particular, polymers with reactive silicon groups (reactive silicon-containing functional groups that can form siloxane bonds through hydrolysis and condensation reactions and crosslink) and oxyalkylene main chains are liquid at room temperature, and the cured products have low modulus and high elongation properties, making them useful in sealants, adhesives, various coating materials, etc.

[0003] A moisture-curable modified silicone (polyoxyalkylene polymer) sealant having reactive silicon groups at the terminals is disclosed, for example, in Patent Document 1. This sealant contains a specific epoxy plasticizer and antioxidant, and therefore maintains adhesion between the cured product and the paint (top coat) even when cured by heat. In order to further improve the adhesion between a sealant containing a polyoxyalkylene polymer and a top coat, an adhesion improver based on an aminosilane or a combination of an aminosilane and an epoxysilane is generally used. Widely known moisture-curing modified silicones with reactive silicon groups at the terminal include those with one methylene group (-CH2-) directly bonded to the reactive silicon group, and those with three methylene groups bonded. Those with one methylene group bonded are particularly useful because they can be cured without the use of catalysts containing harmful tin. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6527599 specification Summary of the Invention [Problem to be solved by the invention]

[0005] However, it has been found that some moisture-curable polyoxyalkylene polymer sealants having reactive silicon groups at the terminals have poor adhesion to the top coat layer. Specifically, -CH2-SiR 1 a (OR 2 ) 3-a When a moisture-curable composition containing a polyoxyalkylene polymer in which one methylene group (-CH2-) is directly bonded to an alkoxysilane terminal group, as shown in the formula (1), is used as a sealant, the adhesion of a top coat layer such as a solvent-based acrylic urethane may be low. 1 a (OR 2 ) 3-a There has been a demand for a method for producing a laminate having excellent adhesion between a cured product of a moisture-curable composition containing a polyoxyalkylene polymer having an alkoxysilane as a terminal group, represented by the formula:

[0006] The present invention has been made in view of the above circumstances, and aims to provide a moisture-curable composition for forming a cured product that exhibits good adhesion to a top coat layer even when a polyoxyalkylene polymer having the above-described terminal group is used; a method for bonding a cured product obtained by curing the moisture-curable composition to a top coat layer; a laminate comprising a substrate, the cured product, and a top coat layer; and a method for producing the same. [Means for solving the problem]

[0007] As a result of extensive research, the present inventors have found that when an aminosilane having two or more amino groups and one or more ethoxy groups is used as an adhesion promoter, the -CH2-SiR 1 a (OR 2 ) 3-a The present inventors have found that the adhesion between a cured product obtained by curing a moisture-curable composition containing a polyoxyalkylene polymer having an alkoxysilane as a terminal group, represented by the formula (I), and a top coat layer is improved, and have completed the present invention.

[0008] That is, the present invention is A moisture-curable composition for forming a cured product to apply a topcoat layer to a surface, comprising: (A) The following general formula (1) Y-[CH2-SiR 1 a (OR 2 ) 3-a ] x (1) (In the formula, Y is an x-valent polymeric group attached through nitrogen, oxygen, or sulfur; R 1 are the same or different monovalent, optionally substituted SiC-bonded hydrocarbon radicals; R 2 are the same or different and are a hydrogen atom or a monovalent, optionally substituted hydrocarbon group; x is an integer between 1 and 10, a is 0, 1, or 2.) Silane-modified polymer A, (B) an aminosilane B having two or more amino groups and one or more alkoxy groups having two or more carbon atoms; A moisture-curable composition comprising:

[0009] The present invention also provides a laminate comprising a substrate, a cured product obtained by curing the moisture-curable composition, and a top coat layer laminated on the cured product.

[0010] -CH2-SiR 1 a (OR 2 ) 3-a When an aminosilane having a methoxy group, an aminosilane containing one amino group, or an aminosilane containing one ethoxy group and one amino group is added as an adhesion improver to a moisture-curable composition containing a polyoxyalkylene polymer (silane-modified polymer A) having an alkoxysilane as a terminal group, the surface of the cured product obtained by curing the crosslinked composition has poor paintability, and even if a top coat layer is applied to the cured product, it is prone to peeling. However, only when an aminosilane having two or more amino groups and one or more alkoxy groups having two or more carbon atoms is added as an adhesion promoter, the paintability improves, and when a top coat layer is applied to the surface of the cured product, the effect of improving adhesion to the top coat layer can be obtained. Furthermore, a laminate comprising a cured product obtained by curing the moisture-curable composition of the present invention and a top coat layer has the property that the adhesion between the cured product and the top coat layer is high and the top coat layer is not easily peeled off.

[0011] The adhesion method of the present invention is a method for adhering a top coat layer to a cured product obtained by curing a moisture-curing composition containing a silane-modified polymer A represented by the following general formula (1), and is characterized by blending an aminosilane B having two or more amino groups and one or more alkoxy groups having two or more carbon atoms into the moisture-curing composition. Y-[CH2-SiR 1 a (OR 2 ) 3-a ]x (1) (In the formula, Y is an x-valent polymeric group attached through nitrogen, oxygen, or sulfur; R 1 are the same or different monovalent, optionally substituted SiC-bonded hydrocarbon radicals; R 2 are the same or different and are a hydrogen atom or a monovalent, optionally substituted hydrocarbon group; x is an integer between 1 and 10, a is 0, 1, or 2.)

[0012] -CH2-SiR 1 a (OR 2 ) 3-a and a moisture-curable composition containing a polyoxyalkylene polymer (silane-modified polymer A) having an alkoxysilane terminal group represented by the formula (I) and a commonly used aminosilane-based adhesion improver, such as an aminosilane having a trimethoxy group, an aminosilane containing one amino group, or an aminosilane containing one ethoxy group and one amino group. Even if a topcoat layer is applied to the surface of the cured product obtained by curing the composition, the topcoat layer has poor adhesion and is prone to peeling. Here, by using an aminosilane having two or more amino groups and one or more alkoxy groups having two or more carbon atoms as the adhesion improver, it is possible to improve the adhesion of the top coat layer to the surface of the cured product.

[0013] The method for producing a laminate of the present invention is a method for producing a laminate by bonding a cured product formed on a substrate and obtained by curing a moisture-curable composition to a top coat layer, the method comprising: The moisture-curable composition is (A) The following general formula (1) Y-[CH2-SiR 1 a (OR 2 ) 3-a ] x (1) (In the formula, Y is an x-valent polymeric group attached through nitrogen, oxygen, or sulfur; R 1 are the same or different monovalent, optionally substituted SiC-bonded hydrocarbon radicals; R 2 are the same or different and are a hydrogen atom or a monovalent, optionally substituted hydrocarbon group; x is an integer between 1 and 10, a is 0, 1, or 2.) Silane-modified polymer A, (B) an aminosilane B having two or more amino groups and one or more alkoxy groups having two or more carbon atoms;

[0014] According to the above production method, a laminate in which the cured product and the top coat layer are firmly bonded can be obtained. DETAILED DESCRIPTION OF THE INVENTION

[0015] The present invention will be described in detail below.

[0016] The moisture-curable composition of the present invention may be in any form or shape as long as it is in the form of at least one liquid and is cured by moisture to finally give a cured product of the composition. 1 a (OR 2 ) 3-a A polyoxyalkylene polymer (silane-modified polymer A) with an alkoxysilane terminal group, as shown in the figure, generates silanols through hydrolysis caused by moisture. A dehydration condensation reaction between these silanols forms a matrix of siloxane bonds, which then hardens.

[0017] <About Silane-Modified Polymer A> The silane-modified polymer A in the present invention contains at least one alkoxysilyl group of the following general formula (1). This may be an alkoxysilyl group linked to one end of the polymer backbone. Preferably, the silane-modified polymer A contains at least one polyoxyalkylene structural unit. Y-[CH2-SiR 1 a (OR 2 ) 3-a ] x (1) (In the formula, Y is an x-valent polymeric group attached through nitrogen, oxygen, or sulfur; R 1 are the same or different monovalent, optionally substituted SiC-bonded hydrocarbon radicals; R 2 are the same or different and are a hydrogen atom or a monovalent, optionally substituted hydrocarbon group; x is an integer between 1 and 10, a is 0, 1, or 2.)

[0018] The silane-modified polymer A is not particularly limited as long as it is an organic polymer, and may be, for example, a polyoxypropylene polymer, a polyoxybutylene polymer, a polyisobutylene polymer, a (meth)acrylic acid ester polymer, or an organic polymer using a plurality of these polymers.

[0019] At least one of the terminal groups of the silane-modified polymer A may be a group represented by the following general formula (2) or (3). -OC(=O)-NH-(CH2)-SiR 1 a (OR 2 ) 3-a (2) -NH-C(=O)-NR'-(CH2)-SiR 1 a (OR 2 ) 3-a (3) (In formula (2) and formula (3), the groups and subscripts have one of the definitions specified above; R' is a monovalent, optionally substituted SiC-bonded hydrocarbon radical.

[0020] The silane-modified polymer A is the main component of the moisture-curable composition, and is a component that forms a cured product by moisture after application. The silane-modified polymer A can be purchased as a commercial product or can be prepared by a common chemical method. The silane-modified polymer A may be a single polymer or a mixture of two or more types. The silane-modified polymer A may be a so-called α-silane-terminated polymer having reactive alkoxysilyl groups attached to adjacent urethane units via methylene spacers. Silane-modified polymer A having such a structure achieves a high cure rate when exposed to air, eliminating the need for toxic tin catalysts and making it safer and less environmentally hazardous. Commercially available α-silane-terminated polymers include GENIOSIL® STP-E10 and STP-E30 from Wacker-Chemie AG.

[0021] base R 1 is a monovalent, optionally substituted SiC-bonded hydrocarbon radical.

[0022] base R 1Examples of are alkyl groups such as methyl, ethyl, n-propyl, isopropyl, 1-n-butyl, 2-n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, tert-pentyl; hexyl groups such as n-hexyl; heptyl groups such as n-heptyl; octyl groups such as n-octyl, isooctyl and 2,2,4-trimethylpentyl; nonyl groups such as n-nonyl; decyl groups such as n-decyl; dodecyl groups such as n-dodecyl. octadecyl groups, such as n-octadecyl; cycloalkyl groups, such as cyclopentyl, cyclohexyl, cycloheptyl, and methylcyclohexyl; alkenyl groups, such as vinyl, 1-propenyl, and 2-propenyl; aryl groups, such as phenyl, naphthyl, anthryl, and phenanthryl; alkaryl groups, such as o-, m-, and p-tolyl, xylyl, and ethylphenyl, and aralkyl groups, such as benzyl, α-, and β-phenylethyl.

[0023] Substituted group R 1 Examples of are haloalkyl groups such as 3,3,3-trifluoro-n-propyl, 2,2,2,2',2',2'-hexafluoroisopropyl and heptafluoroisopropyl groups, and haloaryl groups such as o-, m- and p-chlorophenyl groups.

[0024] Preferably, R 1 preferably comprises a monovalent hydrocarbon group optionally substituted by a halogen atom and having from 1 to 6 carbon atoms, more preferably an alkyl group having 1 or 2 carbon atoms, and more particularly a methyl group.

[0025] base R 2 Examples of groups include the group R 1 is a group specified for base R 2is preferably a hydrogen atom or an alkyl group optionally substituted by a halogen atom and having from 1 to 10 carbon atoms, more preferably an alkyl group having from 1 to 4 carbon atoms, and more particularly a methyl and ethyl group.

[0026] The polymer on which the polymer group Y is based is to be understood in the present invention to be any polymer in which at least 50%, preferably at least 70%, more preferably at least 90% of the total bonds in the main chain are carbon-carbon, carbon-nitrogen, or carbon-oxygen bonds.

[0027] The polymer group Y preferably comprises an organic polymer group, which may comprise as the polymer chain polyoxyalkylenes, such as polyoxyethylene, polyoxypropylene, polyoxybutylene, polyoxytetramethylene, polyoxyethylene-polyoxypropylene copolymers and polyoxypropylene-polyoxybutylene copolymers; hydrocarbon polymers, such as polyisobutylene, polyethylene, or polypropylene and copolymers of polyisobutylene with isoprene; polyisoprene; polyurethanes; polyesters, polyamides; polyacrylates; polymers and polycarbonates, which preferably include -OC(=O)-NH-, -NH-C(=O)O-, -NH-C(=O)-NH-, -NR'-C(=O)-NH-, NH-C(=O)-NR'-, -NHC(=O)-, -C(=O)-NH-, -C(=O)-O-, -OC(=O)-, -OC(=O)-O-, -SC(=O)-NH-, -NH-C(=O)-S-, -C(=O)-S-, -SC(=O)-, -SC(=O)-S-, -C(=O)-, -S-, -O- and -NR'-, which are substituted by one or more groups -[-CH-SiR 1 a (OR 2 ) 3-a ] is combined with

[0028] wherein R' may be the same or different and is an alkyl group, such as methyl, ethyl, n-propyl, isopropyl, 1-n-butyl, 2-n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, or tert-pentyl; a hexyl group, such as n-hexyl; a heptyl group, such as n-heptyl; an octyl group, such as n-octyl, isooctyl, or 2,2,4-trimethylpentyl; a nonyl group, such as n-nonyl; a decyl group, such as n-decyl; or a dodecyl group, such as cycloalkyl groups such as cyclopentyl, cyclohexyl, cycloheptyl and methylcyclohexyl; alkenyl groups such as vinyl, 1-propenyl and 2-propenyl; aryl groups such as phenyl, naphthyl, anthryl and phenanthryl; alkaryl groups such as o-, m-, p-tolyl, xylyl and ethylphenyl, and aralkyl groups such as benzyl, α- and β-phenylethyl.

[0029] Examples of substituted groups R' are haloalkyl groups such as 3,3,3-trifluoro-n-propyl, 2,2,2,2',2',2'-hexafluoroisopropyl and heptafluoroisopropyl groups, and haloaryl groups such as o-, m- and p-chlorophenyl groups. The group R' preferably comprises a monovalent hydrocarbon group optionally substituted by a halogen atom and having from 1 to 6 carbon atoms, more preferably an alkyl group having 1 or 2 carbon atoms, and more particularly a methyl group.

[0030] The group R' may be -CH(COOR")-CH2-COOR", where R" may be the same or different and has the definition given for R'.

[0031] The group R" is preferably an alkyl group having from 1 to 10 carbon atoms, more preferably a methyl group, an ethyl group, or a propyl group.

[0032] More preferably, the group Y in formula (1) comprises a methacrylate group, a urethane group and a polyoxyalkylene group, more preferably a polyoxypropylene-containing urethane group or a polyoxypropylene group.

[0033] The silane-modified polymer A can comprise groups —[(CH)—SiR—, —(CH)—Si ... 1 a (OR 2 ) 3-a ] may be included.

[0034] In one particularly preferred embodiment of the present invention, the silane-modified polymer A is in each case -OC(=O)-NH-(CR 1 2) group or -NH-C(=O)-NR'-(CR 1 2) groups (R' and R 1 has one of the definitions specified above. Includes silane-terminated polyethers and polyurethanes having dimethoxymethylsilyl end groups attached by a .), more particularly silane-terminated polypropylene glycols and polyurethanes.

[0035] The number average molecular weight Mn of the silane-modified polymer A is preferably at least 400, more preferably at least 600, more particularly at least 800, and is preferably less than 30,000, more preferably less than 19,000.

[0036] The viscosity of the silane-modified polymer A is preferably at least 0.2 Pa·s, more preferably at least 1 Pa·s, very preferably at least 5 Pa·s, in each case measured at 20°C, and preferably not more than 1,000 Pa·s, more preferably not more than 700 Pa·s.

[0037] In the case of a first particularly preferred embodiment of the present invention, the silane-modified polymer A comprises, as polymeric group Y, linear or branched polyoxyalkylene groups, more preferably those whose chain ends are linked, preferably by -OC(=O)-NH-, to one or more groups -[(CH2)-SiR 1 a (OR 2 ) 3-a In this case, preferably at least 85%, more preferably at least 90%, and more particularly at least 95% of all chain ends are bonded to a group —[(CH)—SiR by —OC(═O)—NH—. 1 a (OR 2 ) 3-a ] is bound to The polyoxyalkylene group Y has an Mn (number average molecular weight) of 200 to 30,000, preferably 1,000 to 20,000. Suitable processes for preparing such silane-modified polymers (A) and examples of silane-modified polymers (A) themselves are known and are described in publications, including EP 1535940B1 or EP 1896523B1, which are incorporated herein by reference. Corresponding silane-terminated polymers are also commercially available, for example, from Wacker Chemie AG under the name GENIOSIL® STP-E.

[0038] When the silane-modified polymer A is chemically synthesized, it can be synthesized by various known preparation methods, such as, for example, hydrosilylation, addition reactions such as Michael addition, Diels-Alder addition, or the reaction between an isocyanate-functional compound and a compound containing an isocyanate-reactive group.

[0039] The content of the silane-modified polymer A relative to the total composition is not particularly limited, and is preferably in the range of 5 to 90 parts by mass. If it is 5 parts by mass or more, components other than those forming the polymer matrix will not remain in the composition in large quantities, the composition will exhibit sufficient performance, the amount of polymer matrix formed will be sufficient, the required mechanical properties such as tensile strength, elongation, and tear strength will be sufficient, the occurrence of defects in the cured product such as poor adhesion and cracking of the film will be reduced, and the possibility of adverse effects caused by other components will be reduced. A more preferred range is 10 to 60 parts by mass.

[0040] <About Aminosilane B> Aminosilane B is an adhesion promoter having two or more amino groups and one or more alkoxy groups having two or more carbon atoms, and may also function as a curing catalyst. The aminosilane B may have a structure represented by the following general formula (4). D h S i ( OR 7 ) g R 6 f O ( 4 - f - g - h ) / 2 (4) (In the formula, R 6 are monovalent optionally substituted SiC-bonded nitrogen-free hydrocarbon radicals, which may be the same or different; R 7 are optionally substituted hydrocarbon groups having 2 to 18 carbon atoms, which may be the same or different, D are the same or different and represent monovalent SiC-bonded groups having at least one nitrogen atom, and the number of nitrogen atoms contained in one or more Ds is 2 or more; f is 0, 1, 2 or 3, preferably 0 or 1; g is 1, 2 or 3, preferably 2 or 3; h is 1, 2, or 3, preferably 1; However, the sum of f + g + h is 4 or less.)

[0041] The aminosilane B used in the present invention may be either a silane (i.e., a compound of formula (4) where f + g + h = 4) or a siloxane (i.e., a compound of formula (4) where f + g + h ≦ 3), with silanes being preferred.

[0042] base R 6 represents preferably an optionally halogen-substituted hydrocarbon group having 1 to 18 carbon atoms, particularly preferably a hydrocarbon group having 1 to 5 carbon atoms, in particular methyl.

[0043] base R 7 is preferably an optionally halogen-substituted hydrocarbon group having 2 to 18 carbon atoms, particularly preferably a hydrocarbon group containing 2 to 10 carbon atoms, in particular an ethyl group.

[0044] Examples of groups D are groups of the formula H2N(CH2)3-, H2N(CH2)2NH(CH2)3-, H2N(CH2)2NH(CH2)2NH(CH2)3-, H3CNH(CH2)3-, C2H5NH(CH2)3-, C3H7NH(CH2)3-, C4H9NH(CH2)3-, C5H 11 NH(CH2)3-, CH 13 NH(CH2)3-, C7H 15 NH(CH2)3-, H2N(CH2)4-, H2N-CH2-CH(CH3)-CH2-, H2N(CH2)5-, cyclo-C5H9NH(CH2)3-, cyclo-C6H 11 NH(CH2)3-, phenyl-NH(CH2)3-, (CH3)2N(CH2)3-, (C2H5)2N(CH2)3-, (C3H7)2N(CH2)3-, (C4H9)2N(CH2)3-, (C5H 11 )2N(CH2)3-, (C6H 13 )2N(CH2)3-, (C7H 15 )2N(CH2)3-, H2N(CH2)-, H2N(CH2)2NH(CH2)-, H2N(CH2)2NH(CH2)2NH(CH2)-, H3CNH(CH2)-, C2H5NH(CH2)-, C3H7NH(CH2)-, C4H9NH(CH2)-, C5H11 NH(CH2)-, CH 13 NH(CH2)-, C7H 15 NH(CH2)-, cyclo-C5H9NH(CH2)-, cyclo-C6H 11 NH(CH2)-, phenyl-NH(CH2)-, (CH3)2N(CH2)-, (C2H5)2N(CH2)-, (C3H7)2N(CH2)-, (C4H9)2N(CH2)-, (C5H 11 )2N(CH2)-, (C6H 13 )2N(CH2)-, (C7H 15 )2N(CH2)-, and the reaction product of the above-mentioned primary amino group with a compound containing a double bond or an epoxy group reactive towards the primary amino group.

[0045] The group D is preferably H2N(CH2)2NH(CH2)3- or H2N(CH2)2NH(CH2)-.

[0046] Examples of silanes (4) to be used according to the invention are HN(CH)NH(CH)-Si(OCH), HN(CH)NH(CH)-Si(OCH)CH, HN(CH)NH(CH)NH(CH)-Si(OCH) and their partial hydrolysates, HN(CH)NH(CH)-Si(OCH), HN(CH)NH(CH)-Si(OCH)CH or in each case their partial hydrolysates.

[0047] The aminosilane B in the present invention is not limited to the aminosilane monomer of the above formula (4) or a hydrolyzate thereof, but may also be an amino-modified silicone that exerts its effect through a similar mechanism.

[0048] The aminosilane B of the present invention may act as an adhesion promoter and / or water scavenger in the moisture-curable composition according to the present invention and may also function as a curing catalyst or co-catalyst. The aminosilanes B used according to the invention are commercially available products and can be prepared by methods commonly used in chemistry.

[0049] The content of aminosilane B relative to the total composition is not particularly limited, but is preferably in the range of 0.1 to 10 parts by mass. If it is 0.1 part by mass or more, it is possible to promote the hydrolysis and condensation reaction of the silane-modified polymer. On the other hand, if it is less than 0.1 part by mass, the effect of catalyzing the hydrolysis and condensation reaction decreases, and adhesion also decreases. Furthermore, if it is 10 parts by mass or more, the hydrolysis and condensation reaction may progress during storage of the moisture-curable composition, which may lead to gelation and hardening during storage, resulting in poor storage stability. A more preferred range is 0.5 to 5 parts by mass.

[0050] The hydrolysis rate of aminosilanes containing alkoxy groups with two or more carbon atoms, including ethoxy groups, is -CH2-SiR 1 a (OR 2 ) 3-aThe hydrolysis rate is slower than that of the silane-modified polymer A having an alkoxysilane terminal group represented by the formula (I). Therefore, when moisture (e.g., moisture in the air or moisture derived from the substrate to which the moisture-curing composition is applied) is supplied to a moisture-curing composition containing the silane-modified polymer A and the aminosilane B, the alkoxy groups of the silane-modified polymer A are first hydrolyzed to generate silanol groups, and these silanol groups undergo a dehydration condensation reaction to form a matrix, which then hardens. Subsequently, the aminosilane B, which was not incorporated into the matrix of the silane-modified polymer A due to its slow reaction rate, migrates to the surface of the cured product over time. Then, the amino groups derived from the aminosilane B are oriented near the surface of the cured product and interact with the top coat layer applied to the surface, improving the adhesion between the cured product and the top coat layer. The greater the amount of amino groups derived from the aminosilane B exposed on the surface of the cured product, the better the adhesion. For this reason, it is preferable that the aminosilane B has two or more amino groups. Although aminosilane B has a slower hydrolysis rate than silane-modified polymer A, it generates silanol groups through hydrolysis in the same way as silane-modified polymer A. These silanol groups undergo a condensation reaction with the remaining silanol groups of silane-modified polymer A, and are ultimately incorporated into the matrix of silane-modified polymer A, which is thought to improve the adhesion durability between the cured product and the top coat layer.

[0051] In most cured products obtained from moisture-curable compositions containing silane-modified polymers, adhesion to the top coat layer has generally been considered to be good. This is because the silane-modified polymer is hydrolyzed and dehydrated using a tin catalyst (usually -(CH2)3-SiR 1 a (OR 2 ) 3-aThis is presumably because the reaction rate of the silane-modified polymer (which is a polymer with an alkoxysilane terminal group, as shown in Figure 1) was sufficiently fast compared to various aminosilanes. The matrix was formed first by dehydration condensation between the silanol groups of the hydrolyzed silane-modified polymer, and the aminosilane, regardless of its type (particularly the type of alkoxy group), was exposed on the surface of the cured product, thereby improving adhesion to the top coat layer.

[0052] However, -CH2-SiR 1 a (OR 2 ) 3-a A polyoxyalkylene polymer (silane-modified polymer A) having an alkoxysilane terminal group, as shown in the formula (1), has a reaction rate that is relatively slower than other silane-modified polymers that undergo hydrolysis and dehydration condensation reactions in the presence of a tin catalyst, yet a reaction rate comparable to that of many aminosilane-based adhesion improvers (aminosilanes with methoxy groups that have a relatively fast hydrolysis rate). This is thought to have resulted in the problem specific to silane-modified polymer A, namely, poor adhesion. In the case of moisture-curing compositions containing these aminosilane-based adhesion improvers, silane-modified polymer A cures in a state where the aminosilane is incorporated into the silane-modified polymer A matrix before migrating to the silane-modified polymer A surface. This prevents the aminosilane from migrating to the surface of the cured product, preventing it from exerting its adhesiveness-improving effect.

[0053] <Top coat layer> The top coat layer is applied as a paint onto the top (surface) of the cured product for the purpose of imparting weather resistance, light resistance, water resistance, stain resistance, etc. to the coating layer. The type of top coat layer is not particularly limited, and may be, for example, a synthetic resin paint such as an acrylic resin, an acrylic urethane resin, an acrylic silicone resin, a urethane resin, a fluororesin, an alkyd resin, an amino resin, an unsaturated polyester resin, an epoxy resin, a vinyl butyral resin, or a vinyl chloride resin, or an oil-based paint mainly composed of boiled oil, drying oil, or oil varnish, or a cellulose paint mainly composed of nitrocellulose (nitrocellulose), etc. These top coats may be, for example, a strong solvent type, a weak solvent type, or a water-based type. The reaction between the isocyanate group of the acrylic urethane and the amino group of the aminosilane forms a urea bond, which is thought to improve adhesion between the cured silane-modified polymer and the acrylic urethane top coat layer. The intermolecular force between the aminosilane and the acrylic urethane is also thought to be a factor in improving adhesion.

[0054] Examples of additives for the top coat layer composition include ultraviolet absorbers, light stabilizers, light-blocking agents, film-forming aids, stain-resistant hydrophilicity-imparting agents, etc. In addition, in order to match the color tone of the repaired portion, a pigment can be mixed into the coating liquid of the top coat layer composition. As the light-shielding material, calcium carbonate, silica, alumina, magnesium oxide, talc, clay, etc. can be used. As the film-forming aid, Texanol, butyl cellosolve, butyl cellosolve acetate, carbitol, triethylene glycol, etc. can be used. As a hydrophilicity-imparting material for the purpose of stain resistance, organosilicate, fluorine-based surfactant, photocatalytic titanium oxide, etc. can be used. As the solvent, an aliphatic hydrocarbon compound such as mineral spirits can be used.

[0055] <Other ingredients contained in the moisture-curing composition> When the moisture-curable composition containing the silane-modified polymer A and aminosilane B is used as a sealant for various substrates in various applications, the form and composition contents are not limited. For typical applications of a sealant that is compatible with substrates such as building materials and industrial structures, and that is used to apply a topcoat layer to the surface of a cured product, the following composition is preferred. Silane-modified polymer A: 5 to 90 parts by mass Aminosilane B: 0.1 to 10 parts Thixotropy adjuster C: 0 to 20 parts by mass Plasticizer D: 0 to 50 parts by mass Dehydrating agent E: 0 to 10 parts by mass Stabilizer F: 0.01~5 parts by mass Filler G: 0 to 80 parts by mass Curing catalyst H: 0~5 parts by mass However, the parts by mass of each component are parts by mass when the total moisture-curable composition is 100 parts by mass.

[0056] The optionally blended thixotropy regulator C forms a network within the system by its van der Waals forces, thereby thickening the entire system and thereby imparting a certain level of thixotropy to the moisture-curable composition of the present invention.

[0057] Examples of inorganic particles used as a raw material for thixotropy modifier C include inorganic particles such as silica, titanium dioxide, bentonite, zinc oxide, talc, kaolin, mica, vermiculite, magnesium carbonate, calcium carbonate, aluminum silicate, barium silicate, calcium silicate, magnesium silicate, strontium silicate, metal tungstate, magnesium, zeolite, barium sulfate, calcined calcium sulfate, calcium phosphate, fluorapatite, hydroxyapatite, and metal soap. Additionally, composite particles obtained by coating particles with a metal oxide or the like, and modified particles whose particle surfaces have been treated with a compound or the like may also be used.

[0058] Typically, the surfaces of these particles have portions covered with hydrophilic groups such as silanol groups, carbinol groups, or other hydroxyl groups, and portions covered with groups that have been hydrophobized with alkyl groups or other hydrophobic groups. By adjusting the ratio of the hydrophilic group to the hydrophobic group, the aggregation and solubility of the inorganic particles in the system can be controlled.

[0059] Among the inorganic particles, silica is preferably used. Silica is available in various types such as fumed silica, wet silica, and colloidal silica. However, any type of silica particle has hydrophilic silanol groups on the surface, and these silanol groups can be hydrophobized with alkyl groups or the like at any ratio, so it is easy to set the molar ratio of hydrophilic groups to hydrophobic groups on the surface. In addition, silica is preferred because it has an aggregated structure, has high affinity with various oils, and is available easily, economically, and has a wide range of uses.

[0060] The most preferred silica for the present invention is fumed silica. Fumed silica particles have a multi-dimensional aggregate structure, which allows us to control the balance between hydrophilic and hydrophobic groups on the surface and recombine the aggregation units depending on the aggregation level. Furthermore, fumed silica particles have a porous structure, which increases the surface area and enhances the ability to associate and adsorb, making it possible to generate a more stable and uniform system.

[0061] The primary particles, which are the smallest units of fumed silica particles, are usually about 5 to 30 nanometers in size, and the primary particles aggregate to form primary aggregates, that is, secondary particles. The size of primary aggregates is usually about 100 to 400 nanometers. Because the primary particles are fused together by chemical bonds, it is usually difficult to separate the primary aggregates. Furthermore, the primary aggregates form an aggregate structure, which is called a secondary aggregate, or tertiary particle. The size of the secondary aggregates is generally about 10 μm. The aggregation between the primary aggregates in the secondary aggregates is usually due to hydrogen bonds or van der Waals forces, rather than chemical bonds.

[0062] In powder form, fumed silica particles often have the largest aggregated state in secondary aggregates. However, in moisture-curable compositions, secondary aggregates can further aggregate. In one example, the hydrophobized silica of the present invention effectively forms a network with the hydrophobic portion of the silane-terminated polymer and the reactive material (reactive diluent) through van der Waals forces. The force required to separate the aggregates is weaker than the force required to separate the secondary aggregates. In another example, the moisture-curable composition of the present invention has a lower viscosity during application due to the separation of the aggregates when applied with a comb trowel or the like.

[0063] The fumed silica particles are preferably hydrophobized, and the components used for hydrophobization are not particularly limited. For example, the components used for hydrophobization can be hydrophobized by a known method of treating with a halogenated organosilicon such as methyltrichlorosilane, an alkoxysilane such as dimethyldialkoxysilane, a silazane, or a low-molecular-weight methylpolysiloxane.

[0064] The optionally blended thixotropy adjusting agent C is, for example, an organic type such as a hydrogenated castor oil type, an amide type, an oxidized polyethylene type, a vegetable oil polymerized oil type, a surfactant type, etc. The thixotropy adjusting agent C may be a single component or a combination of two or more of these.

[0065] The content of thixotropy regulator C relative to the entire composition is not necessarily required, but is preferably 0.1 to 20 parts by mass. If it exceeds 20 parts by mass, the viscosity of the entire system increases, which may lead to insufficient stirring during production of the moisture-curable composition, resulting in non-uniformity, and significantly reduced workability during application. The content is more preferably 1 to 10 parts by mass, and even more preferably 2 to 5 parts by mass.

[0066] Plasticizer D is a component that has the function of adjusting viscosity and viscosity of the moisture-curable composition of the present invention, and can also function as an additive that adjusts physical properties such as tensile strength and elongation, and improves the flexibility and weather resistance of the cured product. This component is not an essential component for the moisture-curable composition of the present invention unless the above functions or effects are required. Plasticizer D can be purchased as a commercial product or can be prepared by common chemical methods.

[0067] Examples of plasticizers D are phthalate esters, such as dioctyl phthalate, diisooctyl phthalate and diundecyl phthalate; perhydrogenated phthalates, such as diisononyl 1,2-cyclohexanedicarboxylate and dioctyl 1,2-cyclohexanedicarboxylate; adipate esters, such as dioctyl adipate; benzoate esters; glycol esters; esters of saturated alkanediols, such as 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate; phosphate esters; sulfonate esters; polyesters; polyethers, such as polyethylene glycol and polypropylene glycol, preferably having a molar mass of 10,000 to 10,000 g / mol; polystyrene; polybutadiene; polyisobutylene; paraffinic hydrocarbons; and high molecular weight branched hydrocarbons.

[0068] The content of plasticizer D in the entire composition is not necessarily required, but is preferably in the range of 0 to 50 parts by mass. If it exceeds 50 parts by mass, it may cause adverse effects such as deterioration of the physical properties of the coating film, and may cause poor curing or non-curing after application. It is more preferably in the range of 0 to 30 parts by mass.

[0069] The dehydrating agent E is a component that dehydrates the moisture-curable composition of the present invention by capturing water. The dehydrating agent E can be purchased as a commercial product or can be prepared by common chemical methods. The dehydrating agent E may be a single agent or a mixture of two or more agents.

[0070] Examples of dehydrating agents E are silanes, such as vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, O-methylcarbamatemethyl-methyldimethoxysilane, O-methylcarbamatemethyl-trimethoxysilane, O-ethylcarbamatemethyl-methyldiethoxysilane, O-ethylcarbamatemethyl-triethoxysilane and / or their partial condensates, and also orthoesters, such as 1,1,1-trimethoxyethane, 1,1,1-triethoxyethane, trimethoxymethane and triethoxymethane.

[0071] The content of dehydrating agent E relative to the total composition is not necessarily required, but is preferably in the range of 0.01 to 10 parts by mass. If it is less than 0.01 part by mass, the dehydrating effect may be insufficient, and problems such as thickening, gelation, and hardening may occur during production and storage. If it is more than 10 parts by mass, problems such as deterioration of the physical properties of the coating film may occur, and poor hardening or non-hardening may occur after application. A more preferred range is 0.5 to 3.0 parts by mass.

[0072] Stabilizer F is a component that functions as an ultraviolet absorber, antioxidant, heat stabilizer, and light stabilizer for the moisture-curable composition of the present invention, and can also act as a stabilizer against polymer degradation. Stabilizer F can be purchased as a commercial product or can be prepared by conventional chemical methods. The stabilizer F may be a single agent or a mixture of two or more agents.

[0073] The stabilizer F is not limited as long as it exhibits the above-mentioned functions and effects, but is preferably an antioxidant, an ultraviolet stabilizer, or HALS.

[0074] The content of stabilizer F relative to the total composition is preferably in the range of 0.01 to 5 parts by mass. If it is less than 0.01 part by mass, deterioration of the coating film due to ultraviolet rays, heat, oxidation, etc. may occur, while if it exceeds 5 parts by mass, unexpected problems may occur, such as color changes in transparent products. A more preferred range is 0.5 to 2.0 parts by mass.

[0075] The optionally blended filler G is a component that functions as an extender for the moisture-curable composition of the present invention, adjusts viscosity and adjusts physical properties such as tensile strength and elongation, and can also act as a curing accelerator for the coating material due to the moisture it contains. This component is not an essential component for the coating material composition of the present invention if the above functions and actions are not required. Filler G can be purchased as a commercial product or can be prepared by common chemical methods. The filler G may be a single substance or a mixture of two or more substances.

[0076] The filler G may be any filler as long as it exhibits the above-mentioned functions and effects, and examples thereof include, but are not limited to, non-reinforcing fillers, preferably fillers having a BET surface area of ​​up to 50 m / g, such as quartz, silica sand, diatomaceous earth, calcium silicate, zirconium silicate, talc, kaolin, zeolite, metal oxide powders, such as aluminum oxide, titanium oxide, iron oxide, or zinc oxide and / or mixed oxides thereof, barium sulfate, calcium carbonate, gypsum, silicon nitride, silicon carbide, boron nitride, glass powders and polymer powders, such as polyacrylonitrile powder; reinforcing fillers, fillers having a BET surface area of ​​more than 50 m / g, such as pyrogenically prepared silica, precipitated silica, precipitated calcium carbonate, carbon black, such as furnace black and acetylene black, and mixed silicon / aluminum oxides with a high BET surface area; fillers in the form of hollow beads of aluminum trihydroxide, such as those available from 3M Deutschland, Neuss, Germany. magnetic microbeads, examples of which are available from Expancel GmbH under the trade name Zeeospheres™, elastic polymer beads such as those available from AKZONOBEL, Expancel, Sundsvall, Sweden under the trade name EXPANCEL™, or glass beads; fillers in the form of fibres, for example asbestos and also polymer fibres. The above fillers may be hydrophobized, for example, by treatment with organosilanes and / or organosiloxanes, or with stearic acid, or by etherification of hydroxyl groups to alkoxy groups.

[0077] Filler G is preferably calcium carbonate, talc, aluminum hydroxide, and silica, with calcium carbonate being particularly preferred. Preferred grades of calcium carbonate are ground or precipitated, optionally surface-treated with a fatty acid such as stearic acid or a salt thereof. Preferred silica is preferably pyrogenic (fumed) silica.

[0078] Filler G preferably has a water content of less than 1 part by weight, more preferably less than 0.5 parts by weight.

[0079] The content of filler G relative to the total composition is preferably in the range of 0 to 80 parts by mass, and more preferably in the range of 0 to 60 parts by mass. This is because within this range, defects in the coating material, such as poor adhesion and cracking of the coating, are less likely to occur, and the viscosity during production is suitable, allowing for uniform stirring.

[0080] The curing catalyst H is a component that functions as a curing catalyst for the moisture-curable composition of the present invention. This component is not an essential component for the moisture-curable composition of the present invention if the above function or action is not required, but it is an effective component when the reactivity of the silane-terminated modified polymer (A) is low. The curing catalyst H can be purchased as a commercial product or can be prepared by conventional chemical methods. The curing catalyst H may be a single catalyst or a mixture of two or more catalysts.

[0081] The curing catalyst H may be any catalyst as long as it exhibits the above-mentioned functions and effects, and is not limited thereto. Examples of the metal-containing component H include organotitanium and organotin compounds, such as titanate esters, for example, tetrabutyl titanate, tetrapropyl titanate, tetraisopropyl titanate, and titanium tetraacetylacetonate; and tin compounds, for example, dibutyltin dilaurate, dibutyltin maleate, dibutyltin diacetate, dibutyltin dioctanoate, dibutyltin acetylacetonate, dibutyltin oxide, and the corresponding dioctyltin compounds.

[0082] Examples of metal-free curing catalysts H are basic compounds such as triethylamine, tributylamine, 1,4-diazabicyclo[2.2.2]octane, 1,5-diazabicyclo[4.3.0]non-5-ene, 1,8-diazabicyclo[5.4.0]undec-7-ene, N,N-bis-(N,N-dimethyl-2-aminoethyl)methylamine, N,N-dimethylcyclohexylamine, N,N-dimethylphenylamine and N-ethylmorpholinine.

[0083] As curing catalysts H it is likewise possible to use acidic compounds such as phosphoric acid and its esters, toluenesulfonic acid, sulfuric acid, nitric acid, or other organic carboxylic acids such as acetic acid and benzoic acid.

[0084] The content of curing catalyst H relative to the total composition is preferably in the range of 0 to 5 parts by mass. If it exceeds 5 parts by mass, the usable time will be shortened, which may cause poor application, wrinkles on the coating surface, and problems such as thickening, gelation, and hardening during storage. A more preferred range is 0 to 0.2 parts by mass.

[0085] The moisture-curable composition of the present invention may contain any optional components other than those described above, as long as the object of the present invention is achieved. For example, it may contain all other substances such as antifoaming agents, cure rate modifiers, additives, adhesion improvers, and adjuvants. Optionally, a component that improves adhesion, such as an epoxy silane, may also be added.

[0086] The laminate according to the present invention has a configuration in which a cured product is formed by curing the moisture-curable composition on a substrate, and a top coat layer is disposed on the surface of the cured product, so that the substrate and the cured product, and the cured product and the top coat layer are in close contact with each other.

[0087] The moisture-curing composition described above reacts with moisture at room temperature to form a matrix (a three-dimensional network structure) and harden into a cured product. These moisture-curing compositions are used as sealing materials for construction, as well as sealants, adhesives, coatings, and sealants for vehicles such as buses, trucks, passenger cars, and railways, as well as ships and containers. Their use in automobiles and railway vehicles is particularly important from an industrial perspective.

[0088] The automobile manufacturing process is roughly divided into a body assembly process, a painting process, an assembly process, etc. Among these processes, the moisture-curable composition is particularly used in the painting process. The moisture-curable composition is also used in repair processes for vehicles such as automobiles, ships, containers, and the like.

[0089] In painting and repair processes, the curable composition is applied to a substrate (e.g., a car body) for waterproofing, rust prevention, etc., and cured by curing at room temperature. Thereafter, a top coat layer is applied on the car body and the cured moisture-curable composition, and the cured product and the top coat layer are bonded together.

[0090] That is, a laminate is produced using the moisture-curable composition in a method including the following steps 1 to 3.

[0091] (Process 1) Step 1 is a step of applying a moisture-curable composition containing the above-mentioned silane-modified polymer A and aminosilane B to a substrate.

[0092] Examples of the substrate include inorganic substrates such as glass, aluminum, stainless steel, zinc, copper, mortar, vehicle body frames, and vehicle body panels, as well as organic substrates, such as vinyl chloride, acrylic resin, polyester, polyethylene, polypropylene, and polycarbonate.

[0093] The moisture-curable composition to be applied may be a one-component curable composition, or may be a composition prepared by mixing two-component compositions. The coating method is not particularly limited, and can be performed by a known method.

[0094] (Process 2) Step 2 is a step in which the curable composition applied in step 1 is cured at room temperature to be cured.

[0095] The curing temperature is not particularly limited, and is preferably room temperature, more preferably 0°C to 40°C, even more preferably 10°C to 35°C, and most preferably 15°C to 30°C.

[0096] The curing time is not particularly limited as long as at least the surface of the moisture-curable composition is cured, and is preferably 1 to 48 hours, more preferably 2 to 36 hours, even more preferably 5 to 24 hours, and most preferably 12 to 24 hours.

[0097] (Step 3) Step 3 is a step of applying a top coat layer onto the cured product of the curable composition cured in step 2. After applying the top coat layer, a heat curing step can be carried out as necessary. The heat curing temperature can be appropriately selected depending on the properties of the curable composition and the top coat layer, and may be, for example, 100°C or higher, or may be 100°C to 200°C. From the viewpoint of curing the coating material in a short time, the curing temperature is, for example, preferably 160°C to 230°C, and more preferably 180°C to 220°C. The curing time is preferably 10 minutes to 5 hours, more preferably 10 minutes to 3 hours, and even more preferably 10 minutes to 1 hour. [Example]

[0098] The present invention will be specifically explained by showing examples and comparative examples and listing the results in Table 1, but the present invention is not limited to the following examples.

[0099] <How to prepare test specimens to evaluate adhesion with topcoat materials> The moisture-curing compositions obtained in the Examples and Comparative Examples were applied to an aluminum substrate to a film thickness of approximately 2 mm, and then cured for one day under standard conditions (23±2°C, 50±5% RH). An acrylic urethane paint (Retan PG Eco Deep Black, manufactured by Kansai Paint Co., Ltd.) was applied to the cured moisture-curing compositions as a topcoat (i.e., a topcoat layer) with a brush (application amount of approximately 100 g / m). 2 After 15 minutes, the sample is dried at 60°C for 30 minutes and then aged under standard conditions for one day.

[0100] <Method for evaluating adhesion to topcoat materials> The evaluation was carried out in accordance with the cross-cut method of JIS K5600-5-6, and when the evaluation classification was 0 or 1, the adhesion was judged to be acceptable. The coating film on the surface of the test piece was cut into a grid of 100 squares spaced 1 mm apart, adhesive tape was applied to the cuts, and the adhesive tape was then peeled off to evaluate the adhesion based on the degree of peeling, according to the following criteria. Category 0: The edges of the cut are completely smooth and there is no delamination on any of the grid cells. Category 1: There is peeling of more than 0% but not more than 5% in the cross-cut area. Category 2: Peeling of more than 5% and less than 15% occurs in the cross-cut area. Category 3: Peeling of more than 15% and less than 35% occurs in the cross-cut area. Category 4: More than 35% to 65% peeling in the cross-cut area. Category 5: The degree of peeling exceeds Category 4.

[0101] Example 1 The moisture-curable composition used was composed of the following components: As the silane-modified polymer A, GENIOSIL (registered trademark) STP-E30 (viscosity: 30,000 mPa s at 25°C, manufactured by Wacker Chemie AG) was used. In the above general formula (1), Y is a divalent organic polymer group bonded via a urethane group containing an oxyalkylene group as a polymer chain, and R 1 , R 2a = 1, x = 2) was used in a ratio of 25.0 parts by mass to 25.0 parts by mass of PEG (diol type, molecular weight 2000) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. as plasticizer D, 23.5 parts by mass of GENIOSIL (registered trademark) XL10 (vinyltrimethoxysilane) manufactured by Wacker Chemie AG as vinylsilane dehydrating agent E, 1.0 part by mass of Tinuvin B75 manufactured by BASF Japan Ltd. as stabilizer F, 22.0 parts by mass of Softon 2200 manufactured by Bihoku Funka Kogyo Co., Ltd. as filler G, and 22.0 parts by mass of Hakuenka CCR manufactured by Shiraishi Calcium Co., Ltd. as thixotropic modifier C. 2.0 parts by mass of HDK (registered trademark) H18 manufactured by AG and 2.5 parts by mass of GENIOSIL (registered trademark) GF94 (3-(2-aminomethylamino)propyltriethoxysilane) manufactured by the same company as aminosilane B were added and stirred uniformly to prepare moisture-curable composition 1. Y-[CH2-SiR 1 a (OR 2 ) 3-a ] x (1)

[0102] As a result of the evaluation of the topcoat adhesion of the moisture-curable composition 1, the evaluation category was 0, and therefore the adhesion to the topcoat material was deemed to be acceptable.

[0103] <Example 2> Except for using 23.5 parts by mass of Hexamoll (registered trademark) DINCH (registered trademark) (1,2-cyclohexanedicarboxylic acid diisononyl ester) manufactured by BASF Japan Ltd. as plasticizer D, the same ingredients, mass parts, and preparation method as in Example 1 were used to obtain moisture-curable composition 2, which was then evaluated in the same manner.

[0104] As a result of the evaluation of the topcoat adhesion of the moisture-curable composition 2, the evaluation category was 1, and therefore the adhesion to the topcoat material was deemed to be acceptable.

[0105] <Comparative Example 1> As aminosilane B, 2.5 parts by mass of GENIOSIL (registered trademark) GF93 (3-aminopropyltriethoxysilane) manufactured by the same company was used, but the same mass parts and preparation method were used as in Example 1 to obtain moisture-curable composition 3, which was then evaluated in the same manner.

[0106] As a result of the evaluation of the topcoat adhesion of the moisture-curable composition 3, the evaluation category was 5, and therefore the adhesion to the topcoat material was deemed to be unacceptable.

[0107] <Comparative Example 2> As aminosilane B, 2.5 parts by mass of GENIOSIL (registered trademark) GF93 (3-aminopropyltriethoxysilane) manufactured by the same company was used, but the same mass parts and preparation method were used as in Example 2 to obtain moisture-curable composition 4, which was then evaluated in the same manner.

[0108] As a result of the evaluation of the topcoat adhesion of the moisture-curable composition 4, the evaluation category was 5, and therefore the adhesion to the topcoat material was deemed to be unacceptable.

[0109] <Comparative Example 3> As aminosilane B, 2.5 parts by mass of GENIOSIL (registered trademark) GF91 (N-(2-aminoethyl)-3-aminopropyltrimethoxysilane) manufactured by the same company was used, but the same mass parts and preparation method were used as in Example 1 to obtain moisture-curable composition 5, which was then evaluated in the same manner.

[0110] As a result of the evaluation of the topcoat adhesion of the moisture-curable composition 5, the evaluation category was 5, and therefore the adhesion to the topcoat material was deemed to be unacceptable.

[0111] <Comparative Example 4> As aminosilane B, 2.5 parts by mass of GENIOSIL (registered trademark) GF95 (N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane) manufactured by the same company was used, but the same mass parts and preparation method were used as in Example 1 to obtain moisture-curable composition 6, which was then evaluated in the same manner.

[0112] As a result of the evaluation of the topcoat adhesion of the moisture-curable composition 6, the evaluation category was 5, and therefore the adhesion to the topcoat material was deemed to be unacceptable.

[0113] <Comparative Example 5> As aminosilane B, 2.5 parts by mass of GENIOSIL (registered trademark) GF96 (3-aminopropyltrimethoxysilane) manufactured by the same company was used, but the same mass parts and preparation method were used as in Example 1 to obtain moisture-curable composition 7, which was then evaluated in the same manner.

[0114] As a result of the evaluation of the topcoat adhesion of moisture-curable composition 7, the evaluation category was 5, and therefore the adhesion to the topcoat material was deemed to be unacceptable.

[0115] <Comparative Example 6> Except for using 23.5 parts by mass of Hexamoll (registered trademark) DINCH (1,2-cyclohexanedicarboxylic acid diisononyl ester) manufactured by BASF Japan Ltd. as plasticizer D, the same components, parts by mass, and preparation method as in Comparative Example 5 were used to obtain moisture-curable composition 8, which was then evaluated in the same manner.

[0116] As a result of the evaluation of the topcoat adhesion of the moisture-curable composition 8, the evaluation category was 5, and therefore the adhesion to the topcoat material was deemed to be unacceptable.

[0117] <Comparative Example 7> As a silane-modified polymer, GENIOSIL (registered trademark) STP-E35 manufactured by Wacker Chemie AG (viscosity: 30,000 mPa s at 25°C) in which three methylene groups are directly bonded to a reactive silicon group, and in the general formula (5) below, Y is a divalent organic polymer group bonded via a urethane group containing an oxyalkylene group as a polymer chain, and R 1 , R 2 are all methyl groups, a = 0, and x = 2) and 0.2 parts by weight of Neostan U810 (dioctyltin dilaurate) manufactured by Nitto Kasei Co., Ltd. was used as the curing catalyst (J). Except for this, the same components, mass parts, and preparation method as in Comparative Example 5 were used to obtain Moisture-Curable Composition 9, which was then evaluated in the same manner. Y-[(CH2)3-SiR 1 a (OR 2 ) 3-a ] x (5)

[0118] The topcoat adhesion evaluation of moisture-curable composition 9 resulted in a rating of 0, indicating good adhesion to the topcoat material. When using a silane-modified polymer with three methylene groups, the aminosilane contains one amino group, and even compounds containing a methoxy group show good adhesion, but the problem is that they cannot be cured without the use of a curing catalyst containing harmful tin.

[0119] From the above results, it was confirmed that when a moisture-curing composition containing a polyoxyalkylene polymer in which one methylene group is directly bonded to an alkoxysilane terminal group is used as a sealant, blending an aminosilane having two or more amino groups and one or more ethoxy groups improves the adhesion with the top coat layer to the extent that classification 0 or 1 is achieved in the JIS K5600-5-6 cross-cut method.

[0120] [Table 1]

Claims

1. A moisture-curable composition for forming a cured product for applying a topcoat layer to a surface, comprising: (A) a compound represented by the following general formula (1): Y-[CH 2 -SiR 1 a (OR 2 ) 3-a ] x (1) (In the formula, Y has a polymer chain which is polyoxyalkylene, and is linked to a group -[CH 2 -SiR 1 a (OR 2 ) 3-a A group bonded to and R 1 are the same or different, monovalent, optionally substituted, SiC-bonded hydrocarbon radicals; R 2 are the same or different and are a hydrogen atom or a monovalent, optionally substituted, hydrocarbon radical, R' is a monovalent, optionally substituted SiC-bonded hydrocarbon radical; x is an integer from 1 to 10; a is 0, 1, or 2. Silane-modified polymer A, (B) an aminosilane or amino-modified silicone having an alkoxy group having two or more carbon atoms and two or more amino groups, The hydrolysis rate of the component (B) is slower than the hydrolysis rate of the component (A), thereby improving adhesion between the top coat layer and a cured product obtained by curing the moisture-curable composition.

2. A method for producing a laminate by bonding a topcoat layer to a cured product obtained by curing a moisture-curable composition containing a silane-modified polymer A represented by the following general formula (1) and an aminosilane or amino-modified silicone B having an alkoxy group having two or more carbon atoms and two or more amino groups, comprising: applying the moisture-curable composition to a substrate; a step of forming a matrix by hardening the component (A) and a portion of the component (B) with moisture; a step in which the remainder of the component (B) migrates to the surface of the cured product formed in the step of forming the matrix, and amino groups derived from the component (B) are oriented in the vicinity of the surface of the cured product; A step in which the amino groups oriented on the surface of the cured product interact with a topcoat layer; A method comprising: Y-[CH 2 -SiR 1 a (OR 2 ) 3-a ] x (1) (In the formula, Y is a polymeric group having a valence of x attached through nitrogen, oxygen, or sulfur; R 1 are the same or different, monovalent, optionally substituted, SiC-bonded hydrocarbon radicals; R 2 are the same or different and are a hydrogen atom or a monovalent, optionally substituted, hydrocarbon radical, x is an integer from 1 to 10; a is 0, 1, or 2.

3. A method for improving adhesion between a cured product obtained by curing a moisture-curable composition and a top coat layer, comprising the steps of: The moisture-curable composition includes a silane-modified polymer A represented by general formula (1) and an aminosilane or amino-modified silicone B having an alkoxy group having two or more carbon atoms and two or more amino groups, the hydrolysis rate of the aminosilane B is slower than the hydrolysis rate of the silane-modified polymer; applying the moisture-curable composition to a substrate; a step of forming a matrix by hardening the component (A) and a portion of the component (B) with moisture; a step in which the remainder of the component (B) migrates to the surface of the cured product formed in the step of forming the matrix, and amino groups derived from the component (B) are oriented in the vicinity of the surface of the cured product; A step in which the amino groups oriented on the surface of the cured product interact with a topcoat layer; A method comprising: Y-[CH 2 -SiR 1 a (OR 2 ) 3-a ] x (1) (In the formula, Y is a polymeric group having a valence of x attached through nitrogen, oxygen, or sulfur; R 1 are the same or different, monovalent, optionally substituted, SiC-bonded hydrocarbon radicals; R 2 are the same or different and are a hydrogen atom or a monovalent, optionally substituted, hydrocarbon radical, x is an integer from 1 to 10; a is 0, 1, or 2.

Citation Information

Patent Citations

  • Nonstaining sealing composition

    JP1993125271A

  • Aqueous dispersion of organic-inorganic hybrid resin, curable resin composition, coating material, and coated article

    JP2009035711A

  • One-component moisture-curable composition, sealing material consisting of the composition, and solar cell module using the sealing material

    JP2013116976A

  • Method for manufacturing laminate, and laminate

    JP6527599B2

  • JPP6527599B